Activation of adenosine A3 receptors potentiates stimulatory effects of IL-3, SCF, and GM-CSF on mouse granulocyte-macrophage hematopoietic progenitor cells - Hofer, Michal; Pospíšil, Milan; Holá, Jiřina; Štreitová, Denisa; Znojil, Vladimír; Vacek, Antonín (Physiological research, 2009)
Adenosine A(3) receptor agonist N(6)-(3-iodobenzyl)adenosine-5'-N-methyluronamide (IB-MECA) has been tested from the point of view of potentiating the effects of hematopoietic growth factors interleukin-3 (IL-3), stem cell factor (SCF), granulocyte-macrophage colony-stimulating factor (GM-CSF), and granulocyte colony-stimulating factor (G-CSF) on the growth of hematopoietic progenitor cells for granulocytes and macrophages (GM-CFC) in suspension of normal mouse bone marrow cells in vitro. IB-MECA alone induced no GM-CFC growth. Significant elevation of numbers of GM-CFC evoked by the combinations of IB-MECA with IL-3, SCF, or GM-CSF as compared with these growth factors alone has been noted. Combination of IB-MECA with G-CSF did not induce significantly higher numbers of GM-CFC in comparison with G-CSF alone. Joint action of three drugs, namely of IB-MECA + IL-3 + GM-CSF, produced significantly higher numbers of GM-CFC in comparison with the combinations of IB-MECA + IL-3, IB-MECA + GM-CSF, or IL-3 + GM-CSF. These results give evidence of a significant role of selective activation of adenosine A(3) receptors in stimulation of the growth of granulocyte/ macrophage hematopoietic progenitor cells.
Keywords: hepatocytární růstový faktor; interleukin-3; Adenosine; Cell Division; makrofágy; Drug Synergism; financování organizované; hematopoetické kmenové buňky; Financing, Organized; Interleukin-3; zvířata; myši; Cells, Cultured; faktor stimulující granulocyto-makrofágové kolonie; synergismus léků; Hepatocyte Growth Factor; Mice; adenosin; granulocyty; Granulocyte-Macrophage Colony-Stimulating Factor; Male; kultivované buňky; Mice, Inbred Strains; Hematopoietic Stem Cells; Animals; Macrophages; mužské pohlaví; inbrední kmeny myší; Receptor, Adenosine A3; Granulocytes; receptor adenosinový A3; buněčné dělení